2000
DOI: 10.1097/00007691-200004000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective HPLC-Assay for Citalopram and Its Metabolites

Abstract: The racemic selective serotonin reuptake inhibitor citalopram (CIT) is increasingly used for depressive disorders. As both enantiomers of CIT differ in pharmacologic activity and demethylated metabolites might contribute to the antidepressent action of CIT, a stereoselective assay for all active compounds is needed, but will require that pharmacokinetic/pharmacodynamic relationships be investigated. A stereoselective high-performance liquid chromatography (HPLC)-assay (Chirobiotic V column) with UV-detection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…This result opposites the human studies, where the S/R DCIT ratios were somewhat higher than the S/R CIT ratios (Foglia et al, 1997;Rochat et al, 1995a, b;Sidhu et al, 1997;Zheng et al, 2000). Surprisingly, the serum S/R DCIT ratios in the CIT-20 rats were much lower than the serum S/R CIT ratios (0.37 versus 0.83).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This result opposites the human studies, where the S/R DCIT ratios were somewhat higher than the S/R CIT ratios (Foglia et al, 1997;Rochat et al, 1995a, b;Sidhu et al, 1997;Zheng et al, 2000). Surprisingly, the serum S/R DCIT ratios in the CIT-20 rats were much lower than the serum S/R CIT ratios (0.37 versus 0.83).…”
Section: Discussionmentioning
confidence: 57%
“…The S/R ratios of CIT from the groups treated with clinical doses of CIT (i.e. the CIT-10 and CIT-20 groups) can also be compared with S/R CIT ratios from human studies (Foglia et al, 1997;Rochat et al, 1995a, b;Sidhu et al, 1997;Zheng et al, 2000). Our data were not in complete agreement with these studies, where the mean S/R CIT ratios were found in the 0.5 ± 0.7 interval, indicating that the R-enantiomer of CIT was present in higher proportion compared with our data.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, in order to quantitative analyses of the enantiomeric composition of citalopram, various analytical methods have been developed in recent years. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Most of them are involved in the employment of HPLC or supercritical fluid chromatography (SFC), equipped with chiral stationary phases. This study, presents a new, rapid, accurate, precise and the suitable analytical method for seperation of citalopram and the determination of enantiomeric purity of escitalopram with the chiral column composed of silica-based phenylcarbamated β-cyclodextrin (chiral CD-PH).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the monitoring of (−)-(R) and (+)-(S) enantiomers of CIT and of their metabolites, different HPLC (Kosel et al, 1998;Rochat et al, 1995;Zheng et al, 2000) and CE stereoselective methods have been developed. To date, all these methods have dealt with the use of chiral chromatographic columns and none of them use an indirect method based on the derivatization with a chiral reagent.…”
Section: Introductionmentioning
confidence: 99%
“…It is not the aim of this work to determine the presence of citalopram enantiomers, as there are already published methods available for this purpose which have proven to be effective Kosel et al, 1998;Mandrioli et al, 2003;Zheng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%